Intraoperative liposomal bupivacaine for skin graft donor site analgesia: A retrospective cohort study. Issue 5 (August 2021) - Artz, Christina; Ward, Mark A.; Miles, Majel V.P.; Brennan, Phillip; Alexander, Kaitlin M.; Lintner, Alicia; Bright, Andrew; Kahn, Steven A.
Highlights: Liposomal bupivacaine gives effective analgesia through postoperative day one. Donor site pain is significantly less than graft site pain with liposomal bupivacaine. Liposomal bupivacaine prolongs postoperative analgesia for skin graft procedures. Abstract: Introduction: Burn injury and reconstructive operations often result in severe pain, particularly at skin graft donor sites. Traditional local anesthetics administered intraoperatively control pain at donor sites, but the duration of action is short. Liposomal bupivacaine, a novel local anesthetic, can provide sustained-release analgesia for 72 h. The primary aim of this study was to describe the efficacy of liposomal bupivacaine for postoperative donor site pain control for patients undergoing skin graft procedures. Methods: A retrospective cohort study was performed on patients who received a donor site liposomal bupivacaine field block and was compared to a matched control. Patients rated donor site pain on post-operative day 0 and 1, and stated whether the donor or graft site was more painful. Results: Fifty-eight patients were included. Twenty-nine patients received liposomal bupivacaine. Eighty-six percent of patients in the treatment group rated donor site pain as three or less on postoperative day 0 and 1, compared to 3.4% in the control ( p < 0.0001). Also, 76% of patients in the treatment group stated donor site pain was less than graft site pain, compared to 3.4% in the control ( p < 0.0001). Conclusion: Patients who received liposomal bupivacaine reported less postoperative donor site pain and found the donor site to be less bothersome without major complications. Liposomal bupivacaine may be a safe and promising agent for prolonging postoperative analgesia and minimizing donor site pain.